Receptor Oligomerization and Its Relevance for Signaling by Receptors of the Tumor Necrosis Factor Receptor Superfamily - Kucka, Kirstin; Wajant, Harald (Frontiers in Cell and Developmental Biology, 2021)
With the exception of a few signaling incompetent decoy receptors, the receptors of the tumor necrosis factor receptor superfamily (TNFRSF) are signaling competent and engage in signaling pathways resulting in inflammation, proliferation, differentiation, and cell migration and also in cell death induction. TNFRSF receptors (TNFRs) become activated by ligands of the TNF superfamily (TNFSF). TNFSF ligands (TNFLs) occur as trimeric type II transmembrane proteins but often also as soluble ligand trimers released from the membrane-bound form by proteolysis. The signaling competent TNFRs are efficiently activated by the membrane-bound TNFLs. The latter recruit three TNFR molecules, but there is growing evidence that this is not sufficient to trigger all aspects of TNFR signaling; rather, the formed trimeric TNFL–TNFR complexes have to cluster secondarily in the cell-to-cell contact zone for full TNFR activation. With respect to their response to soluble ligand trimers, the signaling competent TNFRs can be subdivided into two groups. TNFRs of one group, designated as category I TNFRs, are robustly activated by soluble ligand trimers. The receptors of a second group (category II TNFRs), however, failed to become properly activated by soluble ligand trimers despite high affinity binding. The limited responsiveness of category II TNFRs to soluble TNFLs can be overcome by physical linkage of two or more soluble ligand trimers or, alternatively, by anchoring the soluble ligand molecules to the cell surface or extracellular matrix. This suggests that category II TNFRs have a limited ability to promote clustering of trimeric TNFL–TNFR complexes outside the context of cell–cell contacts. In this review, we will focus on three aspects on the relevance of receptor oligomerization for TNFR signaling: (i) the structural factors which promote clustering of free and liganded TNFRs, (ii) the signaling pathway specificity of the receptor oligomerization requirement, and (iii) the consequences for the design and development of TNFR agonists.